Cottone's practical infection control in dentistry - Molinari, John A.; Harte, Jennifer A. (Baltimore, Md. : Lippincott William & Wilkins, 2010)
Now in its Third Edition, this book is a primary, comprehensive infection control text for students in the dental professions. Using the latest scientific and clinical evidence and current infection control guidelines, the book presents easy-to-follow protocols as components of a basic infection control routine. This Third Edition has been thoroughly updated and contains more photographs and tables. A glossary of terminology and acronyms appears at the beginning of each chapter
How to choose and use environmental surface disinfectants -- Asepsis considerations of office design and equipment selection -- Management of occupational exposures to blood and other body fluids -- Instrument processing and recirculation -- Role for single-use, disposable items -- Infection control in dental radiography -- Infection control in the dental laboratory -- Medical waste management -- Evaluation of a practical infection dental control program -- Centers for Disease Control and prevention guidelines for infection control in dental health-care settings, 2003 -- Occupational Safety and Health Administration (OSHA) bloodborne pathogens standard
Rev. ed. of: Practical infection control in dentistry / James A. Cottone. 2nd ed. 1996
Includes bibliographical references and index
13
Keywords: Asepsis and antisepsis; Cross infection -- Prevention; Dental offices -- Sanitation; Dentistry